The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s43045-020-00057-6
|View full text |Cite
|
Sign up to set email alerts
|

Rural community attitude towards mental healthcare: a mixed-method study in Khurda district of Odisha, India

Abstract: Background Mental health is a global concern due to its hasty escalation. The shifting social dynamics in rural India intensify care-seeking behaviors, which means immediate action is required. Mental illness, however, is seen as a neglected disorder. This study examined the attitude of rural people towards mental health care in rural Odisha, India. An explanatory mixed-method study was conducted among 395 participants age between 18 to 65 years in two rural blocks of Khurdha district, Odisha. A total of 16 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Various studies were conducted with revealed that attitude toward psychiatrist (27), mental health care (25). However, to our knowledge this is the first ever study which explored the attitudes of rural people toward psychiatric hospital.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various studies were conducted with revealed that attitude toward psychiatrist (27), mental health care (25). However, to our knowledge this is the first ever study which explored the attitudes of rural people toward psychiatric hospital.…”
Section: Discussionmentioning
confidence: 96%
“…There is also a presence of large scale medical institutes such as the All India Institute of Medical Sciences, which provide the local population with good access to mental healthcare. In primary and secondary setting of this study area there is no such mental health care facility is available in this context and for this facility usually people have to depend on tertiary setting with an average distance of 8-10 km (25).…”
Section: Study Settingmentioning
confidence: 99%
“…The relative odds for multiple morbidities is 6.6 times higher for patients over 60 years of age (Pati et al, 2020b). Multimorbidity, along with psychiatric disorders, lead to a substantial rise in healthcare expenditure (Pati et al, 2014(Pati et al, , 2015a(Pati et al, , 2019a(Pati et al, , 2020b and complicates the already limited access to treatment (Pati et al, 2015a(Pati et al, , 2019bMahapatra et al, 2019;Jena et al, 2020). Psychiatric multimorbidity, including dementia, is an emerging global concern among the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The stigma surrounding mental illness, which is a significant impediment to treatment seeking and a contributor in the poor prognosis for those who suffer from it, could conceivably be reduced by the communities' increased awareness of the condition (30)(31)(32). Likewise, the community's favorable perception of mental illness has a significant impact on the lives of survivors (26).…”
Section: Discussionmentioning
confidence: 99%